FROM THEORY TO PRACTICE: IMPLEMENTING WATER MANAGEMENT TECHNOLOGY FOR CLIMATE RESILIENCE: A CASE STUDY IN KARAK DISTRICT - Muhammad Amish; Dr. Asad Ullah; Sahid Zaman; Junaid Ahmad Farooqi (International Journal of Contemporary Issues in Social Sciences, 2024)
The main objective of this research study is to assess the association of water management technology in climate change resilient water management. The research is carried out in three union council of district Karak i.e., village councils (VCs) Sabar Abad , Toor march and kabir kally. Out of the total population of 1324 framers a sample size of 302 framers was proportionally allocated to each VC and selected through random sampling technique. Data was collected through interview schedule. The conceptual framework of the study consisted of one independent variable (water management technology) and one is dependent variable (climate change resilient water management). The variables were measured on three levels Likert Scale. Chi-square test was applied at the bi-variate level to ascertain the association among these study variables. Association between climate change resilient water management with water management technology show that climate change resilient water management exhibited a highly significance association with constructing tank/ponds to store irrigation water (P=0.001), tanks and ponds constructed for water storage are reliable Constructing tanks and ponds can help in capturing and storing rainwater or runoff, which can then be used for irrigation during dry spells or periods of water scarcity induced by climate change. In especially in areas susceptible to climate extremes and fluctuation, the infrastructure used for storing water must be reliable in order to guarantee a steady supply of water for irrigation (P=0.002), and store and treat house hold waste water for irrigation purpose reusing and recycling treated wastewater for agricultural use can reduce the demand on freshwater resources, particularly in regions where water shortage is a result of climate change (P=0.003). These results highlight the value of making infrastructural investments for water distribution and storage, along with incorporating creative solutions like reusing home wastewater. The study emphasizes how local perspectives and expertise influence adaptive water management plans.